Oral health evolution in Brazilian adolescents: comparative analysis of SB Brasil Surveys 2003, 2010 and 2023 - Andreia Maria Araújo DRUMMOND; Thiago Caldeira DINIZ; Raquel Conceição FERREIRA; Viviane Elisângela GOMES; Rafaela da Silveira PINTO; Mara VASCONCELOS; Marcus Vinícius Camargo PRATES; Andrea Maria Duarte VARGAS (Brazilian Oral Research)
Abstract This study aimed to compare the findings of the SB Brasil 2003, 2010, and 2023 surveys and analyze the evolution of caries experience among Brazilian adolescents (aged 15–19 years). A total of 16,832 adolescents were evaluated in 2003, 5,445 in 2010, and 8,054 in 2023. Although the 2010 sample was numerically smaller, all surveys maintained representativeness for Brazil, its regions, and state capitals, following national epidemiological sampling criteria. The DMFT index (Decayed, Missing, and Filled Teeth) and its components were analyzed at the national, regional, and state capital levels, considering socioeconomic and regional disparities. A significant reduction in the mean DMFT index was observed, from 5.51 (2003) to 4.25 (2010) and 3.41 (2023), with more pronounced declines in the Northeast and South regions. The decayed component showed a decrease between 2003 and 2023, while the filled teeth without decay component consistently decreased. Despite these improvements, regional inequalities persist, with the North and Central-West regions reporting higher caries rates and lower access to dental care. These findings highlight notable advancements in adolescent oral health in Brazil, particularly regarding the reduction in caries experience across some regions. However, persistent disparities underscore the need for targeted public health policies to ensure more equitable access to oral healthcare.